Struktur Lapis TitanoNiobat terpilarkan Polimer-{Ti(IV) Okso Hidroksida} - Hari Sutrisno (Jurnal Matematika & Sains, 2003)
The purpose of this research was to incorporate the cation of [Ti8O12(H2O)24]8+ in the interlayer of HTiNbO5 by so-called âChimie Douceâ method. The cation of [Ti8O12(H2O)24]8+ has been tranformed to polymer-{Ti(IV) Oxo Hydroxide} and pillared in the interlayer HTiNbO5. The incorporation of polymer-[Ti(IV) Oxo Hydroxide] in the interlayer HTiNbO5 has been confirmed by powder X-ray diffraction, Scanning Electron Microscopy (SEM) and High Resolution Transmission Electron Microscopy (HRTEM). The exchange of the polymer of {Ti(IV) Oxo Hydroxide} was facilitated by opened layers of butylamine-intercalated complexes.